REMODELING OF THE LEFT VENTRICLE: ONE OR SEVERAL SCENARIOS? - V. V. Kalyuzhin; A. T. Teplyakov; M. A. Solovtsov; E. V. Kalyuzhina; I. D. Bespalova; N. N. Terentyeva (Бюллетень сибирской медицины)
The authors of the review have analyzed papers published on the problem of remodeling of the left ventricle (LV), which is in accordance with a consensus paper from an International Forum on Cardiac Remodeling may be defined as genome expression, molecular, cellular and interstitial changes that are manifested clinically as changes in size, shape and function of the LV after cardiac injury. Remodeling of the LV is often seen as a nonspecific process independent of the nature of the underlying disease (cluster of disease). This approach, contrary to the theory of multimodal response of the myocardium (myocytes and interstitium) on the molecular-genetic, cellular, tissue, and organ levels, largely depending on the nature and duration of the triggering factor, as well as modern ideas about the types of LV remodeling and dividing the latter into serdechadaptive and non-adaptive forms, was the subject of legitimate criticism. Analyzed scenarios the molecular and cellular events, as well as deals with diagnosis of left ventricular remodeling. Discusses the classification of LV remodeling.